Pengembangan Sistem Pelaporan Akuntabilitas Kinerja Instansi Pemerintah Fakultas Ilmu Komputer Universitas Brawijaya - Iman Harie Nawanto; Fajar Pradana; Muhammad Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
One of the efforts to realize a clean and good government is by reporting the performance accountability of government agencies. The report was also carried out at the Faculty of Computer Science, Universitas Brawijaya. The Quality Assurance Group of the Faculty of Computer Science has the responsibility for making the report. The quality assurance team had many problems when making the report. At this time for the manufacture of the report is done using Microsoft Excel with more than 40 sheets. It is not surprising that when the data processing is carried out errors occur such as entering the wrong data or accidentally deleting data. In addition, it is necessary to carry out data processing to find out that the data entered has met the achievement target or not. The current data collection is still done manually by taking data from several fields, so if there is a change in the data from these fields, it is necessary to re-collect the data. Therefore, the authors conducted research by developing an application of a government agency performance accountability system at the scope of the computer science faculty to assist the quality assurance group in preparing government agency performance reports. Website-based applications. The application development method used is the waterfall. This method is very suitable to be used when developing applications whose needs are clear. Based on the results of the needs analysis, there are 428 functional requirements and 1 non-functional requirement. This application is developed using Laravel and Bootstrap framework. In the validation test using black box, the test results are 100% valid. In usability testing using the usability scale system, the results obtained an average score of 70.625 so that it is classified as acceptable. In addition, the compatibility test results that the application can be used on a browser that meets non-functional requirements.